The potential for second generation bio-ethanol production from agro-industrial waste in South Africa - Gikuru, Mwithiga (Academic Journals, 2013)
There has been a sustained and growing interest in the production of liquid fuel from biomass in recent years. South Africa is a large producer of sugar, maize and wheat among other agricultural products that release big quantities of biomass byproducts during postharvest processing operations. This work looks at the energy situation in South Africa and especially the liquid fuel sector and explores the possibility of producing bioethanol from biomass. A brief discussion of the different types of feedstock for bioethanol production is given. A review of possible bio-sources that can be used for bioethanol production with emphasis on those that have potential of replacing conventional fuels with little or minor modification of existing biomass production capacity and trend is presented. Data analysis indicates that the straw from maize, sorghum and wheat can produce up to 601.8 million litres of bioethanol per annum and that it is possible to produce up to 549.4 million litres of bioethanol from sugarcane. The physical ability of mass production from various crop byproducts that are produced in South Africa, as well as the immediately economic effect is also discussed.
Keywords: Bioenergy; bioethanol; cellulose; potential; South Africa; agricultural residue